Vicenin-2 inhibits Wnt/β-catenin signaling and induces apoptosis in HT-29 human colon cancer cell line - Yang D; Zhang X; Zhang W; Rengarajan T (Dove Medical Press, 2018)
Dong Yang,1,* Xiling Zhang,2,* Wencun Zhang,3 Thamaraiselvan Rengarajan4 1Department of Anorectal Surgery, The First People’s Hospital of Lianyungang, Lianyungang, China; 2Department of Anorectal Surgery, Shaanxi Provincial People’s Hospital, Shaanxi, Xi’an, China; 3Department of Anorectal Surgery, The Fourth Hospital of Yu Lin City, Shaanxi Province, China; 4Scigen Research and Innovation, Periyar Technology Business Incubator, Thanjavur, Tamil Nadu, India *These authors contributed equally to this work Background: Colorectal cancer (CRC) is among highest prevailing cancers in the whole world, especially in western countries. For a diverse of reasons, patients prefer naturally occurring dietary substances over synthetic agents to prevent cancer. Vicenin-2 is largely available in a medicinal plant Ocimum sanctum and is an apigenin form, 6,8-di-C-glucoside, which has been reported to have a range of pharmacological values which includes antioxidant, hepatoprotective, anti-inflammatory and anti-cancer. This study was aimed to analyze the anti-proliferative effect of Vicenin-2 on human colon cancer cells via the Wnt/β-catenin signaling inhibition. Methods: MTT assay was used to assess the cell viability at different concentrations and time point. Vicenin-2 at a concentration of 50 μM (IC50) decreased the phosphorylated (inactive) glycogen synthase kinase-3β, cyclin D1, and non-p-β-catenin expressions in HT-29 cells, which were evidenced through western blot analysis. Results: Further, Vincenin-2 reduced the T-cell factor (TCF) / Leukocyte erythroid factor (LEF) reporter activity in HT-29 cells. Vicenin-2 also promoted substantial cell cycle arrest at the G2M phase of HT-29 cells, as well induced apoptosis in HT-29 cells, as revealed through flow cytometric analysis. Furthermore, immunoblot analysis showed that Vicenin-2 treatment enhanced the expression of Cytochrome C, Bax and caspase-3 whereas suppressed the Bcl-2 expression. Conclusion: Together, these results revealed that Vicenin-2 can act as a potent inhibitor of HT-29 cell proliferation and can be used as an agent against CRC. Keywords: colorectal cancer, Vicenin-2, β-catenin, apoptosis, caspase-3